VacBag: packing made easier - Abdul Latiff, Siti Fatimah; Darrold, Hansen Mathew; Mohd. Zamri, Norfarahzila; Andrew, Leviana (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
VacBag is an innovative packing solution designed to streamline the process of organizing and transporting personal belongings. The objectives of VacBag are to simplify packing, reduce luggage weight and volume and enhance convenience for travellers. Novelty in the VacBag lies in its unique design that combines a vacuum-sealed storage bag with built-in compartments and adjustable dividers. By incorporating these features, VacBag allows users to easily organize and pack their belongings while maximizing space efficiency and reducing the overall weight of their luggage. Additionally, VacBag addresses the problem when the airline loses luggage by having a built-in GPS and identification smart chip. The commercialization potential of VacBag is significant due to the increasing demand for efficient packing solutions and the need for optimized baggage handling processes in airports. The benefits of VacBag are distinct as it offers improved handling quality, simplified logistics, and trouble-free storage for travellers. It aims to revolutionize the packing process by offering a unique and innovative solution that simplifies packing, reduces luggage weight and volume, and enhances convenience for travellers.